A Substorm‐Dependent Negative Limit of Non‐Eclipse Surface Charging of a Chinese Geosynchronous Satellite - Zhiyi Fu; Zhenpeng Su; Bin Miao; Zhiyong Wu; Yiren Li; Kai Liu; Xu Shan; Yuming Wang (Space Weather)
Abstract Surface charging is one of the most common causes of spacecraft anomalies. When and to what potential the spacecraft is charged are two important questions in space weather. Here, for a Chinese geosynchronous navigation satellite, we infer the extreme negative surface charging potentials from the ion differential fluxes measured by a low‐energy ion spectrometer. Without the solar eclipse effect away from the midnight, the charging potentials are found to have a negative limit which is determined by the maximum SuperMAG electrojet index in the preceding 2 hr. Such an empirical relation can be reasonably explained by the dependence of 1–50 keV electron fluxes on substorm strength. Similar relations may also exist for other inner magnetospheric spacecraft in the non‐eclipse region, which would be useful for spacecraft engineering and space weather alerts.